2017
DOI: 10.1016/j.chb.2016.12.032
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying health literacy and eHealth literacy using existing instruments and browser-based software for tracking online health information seeking behavior

Abstract: Citizens are increasingly using Internet-based resources to obtain and understand health information at the point of need. The ability to locate, evaluate and use online health information may be influenced by an individual's level of health literacy and eHealth literacy. Those with advanced eHealth literacy skills may utilise more efficient online search strategies and identify higher quality health information resources. This paper describes a study which investigated the associations between health literacy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
82
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 108 publications
(92 citation statements)
references
References 55 publications
(83 reference statements)
1
82
0
Order By: Relevance
“…Online health information is regularly updated [4]. Nowadays, universal and worldwide flow cannot be ignored [5] and search engines are the most effective method to find information [6]. The Internet is also a useful source for people in the medical field for discussions and interactions about medical issues [7].…”
mentioning
confidence: 99%
“…Online health information is regularly updated [4]. Nowadays, universal and worldwide flow cannot be ignored [5] and search engines are the most effective method to find information [6]. The Internet is also a useful source for people in the medical field for discussions and interactions about medical issues [7].…”
mentioning
confidence: 99%
“…Ergo, it was likely that the level of educational attainment for these college students would be high, and consequently eHealth literacy levels would also be high [19].…”
Section: Discussionmentioning
confidence: 99%
“…The popularity of the eHEALS is not without criticism. Though the original instrument showed high correlations with related concepts, more recent studies have indicated a weaker correlation between the eHEALS and Internet use (van der Vaart et al, 2011) and traditional health literacy (Quinn, Bond & Nugent, 2017). Paige et al (2018) also point out that the eHEALS is intended to reflect the Lily Model but the items in the instrument are not reflective of the model's competencies.…”
Section: F Health Literacymentioning
confidence: 99%